Exploring media consumption behavior through the role of social influence and hedonic motivation in anime binge-watching and cosplay participation - Burhan, Panjibrata; Abdullah, Aceng; Priyatna, Centurion Chandratama (Universitas Negeri Malang, 2025)
Anime binge-watching has emerged as a significant cultural trend, yet the pathway from this activity to active participation in cosplay remains insufficiently studied. This research explores how social influence and hedonic motivation contribute to this transition, offering broader insights into media consumption and fan engagement behaviors. Employing a quantitative survey approach, data were collected from 412 followers of Rafcreative, an Instagram-based community actively engaged in anime and cosplay events. The study utilizes path analysis through AMOS to examine the direct and indirect effects of social influence and hedonic motivation on cosplay participation, with binge-watching behavior as a mediating factor. The findings show that anime binge-watching plays a key mediating role between both social influence and hedonic motivation about cosplay engagement. Social influence positively impacts both binge-watching and cosplay participation, while hedonic motivation exerts an even more substantial influence on binge-watching and indirectly enhances cosplay involvement. These results underscore the importance of enjoyment-driven and socially influenced behaviors in shaping the experiences of anime fans. The study advances our understanding of fan engagement by outlining how media consumption can evolve into participatory practices, offering practical implications for event organizers and media producers seeking to build deeper connections within anime fan communities.